Developing reproducible lidar classifications for Greek archaeology: assessing an area-based verification strategy for lidar-based archaeological prospection in the Cyclades, Greece - Manquen, Brody W.; Garrison, Thomas G.; Knodell, Alex R.; Athanasoulis, Demetrios (Journal of Greek Archaeology, 2025)
Over the last decade, archaeologists around the world have increasingly added lidar data from aerial and terrestrial platforms to their project toolkit. As lidar-based archaeology has proliferated, experience with the technology has not been evenly distributed. The technology garnered recognition for its ability to precisely map ground surfaces under dense canopy in the heavily forested regions of Mesoamerica, Southeast Asia, and parts of Europe.1 In the Maya Lowlands, researchers acknowledged the revolutionary nature of the technology early on.2 Subsequent years of use have allowed its applications to mature, as seen in studies analyzing patterns of social inequality and redefining ancient Maya rural land use.3 Importantly, this maturation has allowed for the refinement of survey methods as archaeologists have confronted the mistakes of early applications, for example issues of mismatching verification procedures and representational issues in classified datasets.